Race, Income, and Survival in Stage III Colon Cancer: CALGB 89803 (Alliance). Issue 3 (12th April 2021) - Lee, Seohyuk; Zhang, Sui; Ma, Chao; Ou, Fang-Shu; Wolfe, Eric G; Ogino, Shuji; Niedzwiecki, Donna; Saltz, Leonard B; Mayer, Robert J; Mowat, Rex B; Whittom, Renaud; Hantel, Alexander; et al.
Abstract: Background: Disparities in colon cancer outcomes have been reported across race and socioeconomic status, which may reflect, in part, access to care. We sought to assess the influences of race and median household income (MHI) on outcomes among colon cancer patients with similar access to care. Methods: We conducted a prospective, observational study of 1206 stage III colon cancer patients enrolled in the CALGB 89803 randomized adjuvant chemotherapy trial. Race was self-reported by 1116 White and 90 Black patients at study enrollment; MHI was determined by matching 973 patients' home zip codes with publicly available US Census 2000 data. Multivariate analyses were adjusted for baseline sociodemographic, clinical, dietary, and lifestyle factors. All statistical tests were 2-sided. Results: Over a median follow-up of 7.7 years, the adjusted hazard ratios for Blacks (compared with Whites) were 0.94 (95% confidence interval [CI] = 0.66 to 1.35, P = .75) for disease-free survival, 0.91 (95% CI = 0.62 to 1.35, P = .65) for recurrence-free survival, and 1.07 (95% CI = 0.73 to 1.57, P = .73) for overall survival. Relative to patients in the highest MHI quartile, the adjusted hazard ratios for patients in the lowest quartile were 0.90 (95% CI = 0.67 to 1.19, P trend = .18) for disease-free survival, 0.89 (95% CI = 0.66 to 1.22, P trend = .14) for recurrence-free survival, and 0.87 (95% CI = 0.63 to 1.19, P trend = .23) for overall survival. Conclusions: In this study of patients with similar health-care access, no statistically significant differences in outcomes were found by race or MHI. The substantial gaps in outcomes previously observed by race and MHI may not be rooted in differences in tumor biology but rather in access to quality care.